Plato - Plato (Princeton, 1942)
Some twenty four hundred years ago that part of the world which then represented Western Civilization was divided into two opposing leagues of states. One leagues was headed but a seagoing, trading democracy, mistress of marine empire of colonies and more or less subject states, scattered through the neighboring seas. The other was led by an inland, military aristocracy, conqueror of considerable territory close around herself and ally of whatever states feared the spread of democratic imperialism. The democracy was Athens, then at the height of her expanding pride and glory. The aristocracy was Sparta, conservatives and tenacious, holding on to all that had ever been hers. Athens had a matchless fleet; Sparta an army without equal on shore.
Keywords: Ideology